Factors Affecting the Occupancy of Gaur (Bos gaurus) During Winter Season in Parsa National Park, Nepal - Bishnu Prasad Bhattarai; Hem Bahadur Katuwal; Sandeep Regmi; Bishnu Aryal; Krishna Tamang; Sabin KC; Amrit Nepali; Shivish Bhandari; Amir Basnet; Pradip Kandel; Chandu Paneru; Bishal Subedi; et al. (Ecology and Evolution)
ABSTRACT Gaur (Bos gaurus) is a globally vulnerable species with a decline of more than 80% of their global distribution in the past 100 years. Understanding the species distribution pattern and associated factors is essential for developing effective conservation strategies. We examined the effects of forest area, human detections, presence of tiger (Panthera tigris), presence of competing species like Asian elephant (Elephas maximus), and sambar deer (Rusa unicolor), and distance to water, on gaur occupancy in Parsa National Park (PNP), Nepal, using camera traps which were deployed at 67 locations from December 2022 to March 2023. We used single season single species occupancy modeling to estimate the relationship of selected covariates with gaur occupancy. We recorded a total of 54 gaur detections in our study. We found that gaur occupancy had a significant positive association with the distance to water bodies and was negatively associated with forest area and the presence of elephants; however, there was no significant association with number of humans detected, or the presence of tigers, or sambar deers. Gaur had greater detection probabilities in southcentral portions of PNP, i.e., flat plains and areas near the Chure region and the lowest detection probabilities in the eastern and western parts of PNP. These findings highlight the importance of considering eco‐environmental factors in the management and conservation of gaur, particularly in human‐dominated landscapes. We recommend further multi‐seasonal studies to better understand the dynamic interactions between gaur, their environment, and other species, to inform effective conservation strategies.